The organisational and psychosocial aspekts of adherence to diabetes therapy - Rolinska, Agnieszka (Journal of Education, Health and Sport, 2020)
The global prevalence of diabetes is on the rise. The World Health Organization (WHO) estimates that diabetes will be the 7th leading cause of death in 2030. People with untreated or inadequately controlled diabetes are at greater risk of developing complications from SARS-CoV-2 infection in the COVID-19 pandemic. Adapting to therapy for diabetes is a complex process. Numerous studies show the importance of many indirect, non-clinical factors in the treatment of patients with diabetes. It is necessary to develop methods that facilitate the selection of patients at risk of non-adherence to the disease due to psychological, organizational and/ or socio-demographic factors, including in the medical tele-counseling system currently intensively developing in diabetology.